PENGARUH JAM BELAJAR DAN BEBAN TUGAS AKADEMIK TERHADAP BURNOUT AKADEMIK SISWA SMK SWASTA TELADAN PEMATANGSIANTAR - Monica Evelina Silaban; Benjamin Albert Simamora; Anggun Tiur Ida Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of study hours at school and academic workload on students’ burnoutacademic at SMK Swasta Teladan Pematangsiantar in the 2025/2026 academic year. This research employed a quantitative approach with an associative research design. The population consisted of 412 students, with a sample of 203 students selected using proportionate stratified random sampling technique. Data were collected through questionnaires using a Likert scale. The data analysis techniques included multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that: (1) study hours at school have a positive and significant effect on students’ burnout academic, with a t-value of 7.725 and a significance level of 0.000 < 0.05; (2) academic workload has a positive and significant effect on students’ burnout academic, with a t-value of 9.997 and a significance level of 0.000 < 0.05; (3) study hours at school and academic workload simultaneously have a significant effect on students’ burnout academic, with an F-value of 74.304 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.765, indicating that 76.5% of the variation in burnout academic can be explained by study hours and academic workload, while the remaining 23.5% is influenced by other factors outside this study. Based on these findings, it can be concluded that higher study hours at school and greater academic workload lead to higher levels of students’ burnout academic. Therefore, it is necessary to manage study hours and academic workload proportionally to minimize the level of students’ burnout academic.